Donor demands and uses for evidence of research impact - the case of the Consultative Group on International Agricultural Research (CGIAR) - Raitzer, David A.; Winkel, Klaus (CGIAR System Organization, 2005)
Ex post impact assessment (epIA) is often promoted as a method of illustrating to funding bodies that agricultural research investments are effectively contributing to the achievement of development goals. In response, impact assessors have produced a great deal of evidence that international agricultural research is an efficient and effective form of investment. Despite these results, international agricultural research, including the activities of the Centres of the CGIAR, has at times faced funding shortages. This may indicate that the evidence produced has not been entirely persuasive. To help foster a more demand-led approach to epIA, this analysis investigates the information demands of CGIAR Members (donors), the primary audience for accountability–oriented epIA studies. Two methods were applied to analyse information demands and uses. First, an email survey of all CGIAR Members was conducted, so as to ascertain preferences for different epIA approaches, methods, and metrics. Subsequently, a series of interviews of donor representatives was used to explore in more detail how the results from epIA contribute to funding decisions. The 24 email survey responses received from 22 Member agencies indicate high demand for impact related information. Analyses of impact “far down the impact pathway” with metrics directly related to poverty and improved livelihoods are most frequently claimed to be most useful. Similarly, a majority of respondents report that the “magnitude and distribution of benefits” is the primary determinant of the use of epIA findings. EpIA conduct by an external assessor is reported as important for credibility by most respondents. Follow-up interviews of representatives of 26 CGIAR Members illustrate that agricultural research funding decisions within Member agencies are complex, and the consideration of patterns of past impact in these deliberations is often less than central. Other factors, such as political priorities, perceptions of scientific quality, and desires for funding continuity also play prominent roles in these decisions, and decision-makers face an onslaught of many forms of information apart from epIA findings. In this context, brief summaries of epIA results are critical to capture attention, and the influence of findings is often indirect and “conceptual.” Despite the indirect nature of this influence, the interviews reiterated strong demands for evidence of impact. A number of Members indicated that the transparency of impact studies could be improved, as certain analyses have been assumption-laden, and sufficient details about the assessed research have not been provided in some cases. These audiences also appear to demand epIA of a broader range of research activities, as “comprehensiveness of coverage” received 2 relatively low ratings. Finally, a greater focus on poverty-related metrics and the distribution of assessed benefits was demanded by a large proportion of interviewees. Responses are compared with patterns documented in the broader evaluation literature. The observations of the present study are generally consistent with prior findings that indirect use is predominant. In addition, the information preferences observed, when compared with approaches advocated for internal feedback in the evaluation literature, suggest that the information demands of donors may differ from those of internal audiences.